Profitability of Small Scale Broiler Production in Onitsha North Local Government Area of Anambra State, Nigeria - IKE, P.C.; Ugwumba, C.O.A. (International Journal of Poultry Science, 2011)
This study was carried out to establish the profitability of small scale broiler production in Onitsha north local government area of Anambra state, Nigeria. The specific objectives are to determine the effects of socioeconomic characteristics of broiler producers on output and to estimate the returns of broiler enterprise in the study area. Primary data were collected from one hundred and thirty five (135) broiler farmers by use of well structured questionnaire. Descriptive and inferential statistical tools such as means, percentages and multiple regression analysis as well as enterprise budget were applied to analyze the data collected for the study. Findings indicated that most of the respondents (70%) were males and same were aged between 36-55 years while most of the farmers have long years of experience in broiler production. Regression estimates indicated that six variables including experience in broiler production, farming status, access to credit, labour, number of Day-old chicks and quantity of feeds exerted statistically significant influence on broiler production with an R2 of 0.79 and an F-ratio of 39.1. A single broiler nurtured to maturity had a total cost of 942.14 made up of 30.40 fixed cost and 911.74 variable cost. With gross revenue per bird at 1334.00, net revenue of 391.86 per bird was calculated and this gave a net margin-to-cost ratio of 0.42 which implies that a 1.00 investment in broiler production all things being equal would yield 0.42 in return. It is the recommendation of this study that state and local governments should improve their credit delivery to farmers as this will go a long way in improving output.